MEMULIHKAN KEHARMONISAN KELUARGA DARI JERATAN JUDI ONLINE: SOLUSI PRAKTIS DENGAN INTEGRASI TEORI SISTEM KELUARGA BOWEN - Sugitanata, Arif (Center of Gender Studies and Child of State Islamic Institute of Metro, 2024)
The main objective in this study is to explain the efforts in restoring family harmony as a result of online gambling addiction behavior using Murray Bowen's family system theory as an analytical framework. This research is a literature study with primary data from relevant journals and books to understand how to repair relationships damaged by gambling addiction and restore family harmony. The results show that; first, online gambling addiction has damaged the trust, finances, and mental health of family members. Second, recovery efforts require acknowledging the problem, professional help, family support, and engaging in positive activities. Family therapy and community support are essential in rebuilding trust and harmony. Third, healthy financial management and improved interpersonal relationships are also important parts of the recovery process. Meanwhile, the implementation of Bowen's family systems theory provides insights into family dynamics, highlighting the importance of understanding and intervening at the individual and family levels to restore harmony. This research generates practical recommendations for individuals, families, and professionals involved in online gambling addiction recovery, emphasizing a holistic approach involving emotional support, financial management, and improved interpersonal relationships. Keywords: Family System, Murray Bowen, Family, Online Gambling, Harmony Abstrak Tujuan utama dalam penelitian ini adalah menjelaskan upaya dalam pemulihan keharmonisan keluarga sebagai dampak dari perilaku kecanduan judi online menggunakan teori sistem keluarga Murray Bowen sebagai kerangka analisis. Penelitian ini merupakan studi kepustakaan dengan data primernya dari jurnal dan buku relevan untuk memahami cara memperbaiki hubungan yang rusak oleh kecanduan judi dan mengembalikan keharmonisan keluarga. Hasil penelitian menunjukkan bahwa; pertama, kecanduan judi online telah merusak kepercayaan, keuangan, dan kesehatan mental anggota keluarga. Kedua, upaya pemulihan memerlukan pengakuan masalah, bantuan profesional, dukungan keluarga, dan terlibat dalam kegiatan positif. Terapi keluarga dan dukungan komunitas sangat penting dalam membangun kembali kepercayaan dan keharmonisan. Ketiga, pengelolaan keuangan yang sehat dan perbaikan hubungan interpersonal juga merupakan bagian penting dari proses pemulihan. Sementara itu, implementasi teori sistem keluarga Bowen memberikan wawasan pada dinamika keluarga, menyoroti pentingnya pemahaman dan intervensi pada tingkat individu dan keluarga untuk memulihkan keharmonisan. Penelitian ini menghasilkan rekomendasi praktis untuk individu, keluarga, dan profesional yang terlibat dalam pemulihan kecanduan judi online, menekankan pendekatan holistik yang melibatkan dukungan emosional, pengelolaan keuangan, dan perbaikan hubungan interpersonal. Kata Kunci: Sistem Keluarga, Murray Bowen, Keluarga, Judi Online, Keharmonisan